First 1000 Days of Life: Consequences of Antibiotics on Gut Microbiota - Aires, Julio (Frontiers in Microbiology, 2021)
The developmental origin of health and disease highlights the importance of the period of the first 1000 days (from conception to 2 years) of life. In particular, the process of gut microbiota establishment occurs within this time window. Therefore, determinants interfering with neonatal gut establishment may disrupt its physiological functions and potentially lead to negative health outcomes. Antibiotics are among perinatal determinants that can directly or indirectly affect the pattern of gut bacterial colonization, with a long-lasting impact on intestinal ecosystem functions. In this review, we will examine the impact of antibiotics on the intestinal microbiota during the perinatal period and first years of life, a key interval for development of an individual’s health capital. Further, we will discuss the role of antibiotics during short- and long-term dysbiosis and their associated health consequences.